1987
DOI: 10.1007/bf00332184
|View full text |Cite
|
Sign up to set email alerts
|

Specific gene amplification associated with consistent chromosomal abnormality in independently established multidrug-resistant Chinese hamster ovary cells

Abstract: Multidrug-resistant (MDR) Chinese hamster ovary (CHO) cell lines were established by selection for resistance to the toxicities of vinblastine (VB) and Adriamycin (AD) in progressively increasing drug concentrations. These cell lines have amplified the DNA sequence that has previously been shown to be amplified in another MDR CHO cell line which was selected with vincristine (VC). An overproduced 4.5 kb mRNA was detected in these MDR cell lines. We report here that the levels of DNA amplification and the 4.5 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…These results, consistent with our initial observation (35), indicate that the amplified DNAs in the three independently established MDR CHO cell lines are distally localized on the chromosome where the single-copy sequence resides. These observations are also consistent with the fact that many drug-resistant Chinese hamster variants contain amplified DNA (22,(45)(46)(47).…”
Section: Materuils and Methodssupporting
confidence: 81%
See 4 more Smart Citations
“…These results, consistent with our initial observation (35), indicate that the amplified DNAs in the three independently established MDR CHO cell lines are distally localized on the chromosome where the single-copy sequence resides. These observations are also consistent with the fact that many drug-resistant Chinese hamster variants contain amplified DNA (22,(45)(46)(47).…”
Section: Materuils and Methodssupporting
confidence: 81%
“…Southern blot hybridizations have shown that both P-gp (35,42) and gene class 5 sequences (unpublished data) are coamplified 30-to 40- Indeed, we found that the Z7 marker chromosome (M) gained an additional segment with a size approximating that of the missing part in chromosome lq. Furthermore, the Giemsabanding pattern in the Z7 addition matched that of the distal portion of chromosome lq.…”
Section: Materuils and Methodsmentioning
confidence: 70%
See 3 more Smart Citations